Phenotyping Cowpeas for Adaptation to Drought - Hall, Anthony (Frontiers in Physiology, 2012)
Methods for phenotyping cowpeas for adaptation to drought are reviewed. Key factors involve achieving optimal time of flowering and cycle length, and appropriate morphology for different types of cultivars as they relate to their utilization for dry grain, hay, and fresh pea production. Strong resistance to vegetative-stage drought is available and should be incorporated. The extreme ability of extra-early erect cowpea cultivars to escape terminal drought should be exploited in zones with very short rainfall seasons. In zones with the possibility of limited rainfall in the middle of the growing season, resistance to mid-season drought, and the delayed-leaf-senescence trait can be valuable. Breeding for water-use efficiency, deeper rooting, and heat tolerance are discussed. Diseases and pests that influence adaptation to drought are considered. Resistance to the organism causing ashy stem blight disease should be incorporated because this disease can destroy cowpea seedlings under hot, dry soil conditions. The value of varietal intercrops with contrasting types of cowpea cultivars in enhancing adaptation to drought is described. Implications of cowpea/cereal rotations for cowpea breeding are discussed. Breeding strategies for enhancing cowpea adaptation to drought are described.